On Visual Arts and Cultural Regionalism in Alsace from the Perspective of a Transylvanian Art Historian - Ana-Magdalena Petraru (Anastasis: Research in Medieval Culture and Art)
Book review: Valentin Trifescu, Geografii artistice și regionalism în istoriografia de artă din Alsacia interbelică/ , Artistic Geographies and Regionalism in Art Historiography in Interwar Alsace, foreword by Andrei-Corbea Hoișie, preface by Jean-Noël Grandhomme, 2nd revised edition, Ed. Școala Ardeleană, 2019, 250 pages.